Students' perceptions of a near-peer Objective Structured Clinical Examination (OSCE) in medical imaging. Issue 1 (February 2020) - Taylor, D.; Quick, S.
Abstract: Introduction: Near-peer learning, where peers from more senior year levels teach more junior peers is a popular teaching strategy in healthcare education. There is an emerging trend to utilise this teaching strategy in preparing students for Objective Structured Clinical Examinations (OSCEs) in the form of near-peer led formative OSCEs (NP-OSCE). However, there is little exploration of this teaching strategy in medical imaging education, nor how students perceive NP-OSCEs as beneficial to their learning. This study addresses this gap. Methods: Using a students as partners inquiry approach, 47 near-peer learners' (NPLs) and 6 near-peer teachers' (NPTs) perceptions of participating in a NP-OSCE were examined using an anonymous self-report questionnaire. Results: NPLs reported that participating in the immersive NP-OSCE helped their performance in the summative OSCE by helping with their preparedness; including understanding expectations, experiencing emotions and being able to identify gaps in their knowledge and skills, which they then used to direct their revision in a manner that demonstrated the development of skills in evaluative judgement. There were mixed findings regarding the impact the NP-OSCE had on NPLs' levels of anxiety. NPTs also found the NP-OSCE beneficial for identifying gaps in their own knowledge and skills, yet found taking on the role of an examiner challenging. Conclusion: Students perceive NP-OSCEs as a valuable learning activity that helps them prepare for their OSCEs by providing a student perspective of an authentic immersive learning experience. NP-OSCEs enable students to focus their revision and develop skills in evaluative judgement. Implications for practice: Educators should consider including NP-OSCEs in their medical imaging curriculum as students perceive it as a valuable learning experience that assists them to prepare for their OSCE.